Cytoplasmic dynein binds dynactin through a direct interaction between the intermediate chains and p150Glued (The Rockefeller University Press, 1995)
Cytoplasmic dynein is a retrograde microtubule motor thought to participate in organelle transport and some aspects of minus end- directed chromosome movement. The mechanism of binding to organelles and kinetochores is unknown. Based on homology with the Chlamydomonas flagellar outer arm dynein intermediate chains (ICs), we proposed a role for the cytoplasmic dynein ICs in linking the motor protein to organelles and kinetochores. In this study two different IC isoforms were used in blot overlay and immunoprecipitation assays to identify IC- binding partners. In overlays of complex protein samples, the ICs bound specifically to polypeptides of 150 and 135 kD, identified as the p150Glued doublet of the dynactin complex. In reciprocal overlay assays, p150Glued specifically recognized the ICs. Immunoprecipitations from total Rat2 cell extracts, rat brain cytosol, and rat brain membranes further identified the dynactin complex as a specific target for IC binding. using truncation mutants, the sites of interaction were mapped to amino acids 1-123 of IC-1A and amino acids 200-811 of p150Glued. While cytoplasmic dynein and dynactin have been implicated in a common pathway by genetic analysis, our findings identify a direct interaction between two specific component polypeptides and support a role for dynactin as a dynein "receptor". Our data also suggest, however, that this interaction must be highly regulated.